ETUDE BOTANIQUE, EVALUATION DE L’ACTIVITE ANTIFONGIQUE DES FEUILLES DE ACANTHOSPERMUM HISPIDUM DC., (ASTERACEAE) SUR LA CROISSANCE IN VITRO DE CANDIDA ALBICANS ET ETUDE DE LA TOXICITE SUR LES CELLULES HUMAINES HFF - Yapi, Basile A.; Gnahoue, Goueh; Camara, Djeneb; Zirihi, Guédé N. (European Scientific Journal, ESJ, 2015)
After an ethnobotanical survey conducted in the Autonomous District of Abidjan (Ivory Coast), we found that Acanthospermum hispidum is one of the best selling plants and the most requested by the actors of traditional medicine. This study was not only initiated to facilitate the recognition of the plant in the field by highlighting its most outstanding botanical characters but also to enjoy its antimicrobial activity on the growth of Candida albicans and its in vitro toxicity to HFF human cells. Botanically, this species is remarkable for its invasiveness and the presence of stiff hairs on all its organs and very spiny achenes. The microbiological test results showed that only the ethanolic fraction (EE70%) has an effective inhibitory activity on the growth of C. albicans after 72 hours of incubation at 30°C. The EE70% fungicide is on C. albicans with CMF = 25 mg/ml. The IC50 of the EE70% A. hispidum C. albicans is 1500 μg/ml, at this concentration; the toxicity tests showed that the plant is not toxic to human cells.